Pengaruh Store Atmosphere dan Lokasi Terhadap Kepuasan Pelanggan Melalui Keputusan Pembelian Pada Warung Parikaton Malang - Alvia Dwi Cahyaningrum; Eka Farida; Ita Athia (UNIVERSITAS ISLAM MALANG, 2023)
Abstract This study aims to determine the effect of store atmosphere, product quality, location on customer satisfaction through purchasing decisions. The population in this study were all customers of Warung Parikaton Malang. The sampling method in this study used a purposive sampling method. Quantitative analysis was performed using SmartPLS. In this study, the results showed that the store atmosphere, product quality, and location did not significantly influence purchasing decisions. Store atmosphere and product quality have no significant effect on customer satisfaction. Location has a significant effect on customer satisfaction, and customer satisfaction has a significant effect on purchasing decisions. In addition, there is an indirect effect of store atmosphere and product quality which does not significantly affect customer satisfaction through customer purchasing decisions. Meanwhile, location has a significant effect on customer satisfaction through purchasing decisions. Keywords: Store Atmosphere, Product Quality, Location, Customer Satisfaction, Purchasing Decisions